Dictionary of energy - Cleveland, Cutler J.; Morris, Christopher G. (Elsevier, 2015)
The Dictionary of Energy, Second Edition is a comprehensive and authoritative reference on all aspects of energy and its role in society. Edited by Cutler J. Cleveland and Christopher Morris, the editors of Handbook of Energy, Volumes 1 and 2, this authoritative resource comes at a time when the topic of energy prices, resources and environmental impacts are at the forefront of news stories and political discussions. The Second Edition of Dictionary of Energy contains over 10,000 terms, across 40 key subject areas in energy (e.g. solar, oil & gas, economics, models, policy, basic concepts, su.- Resumé vydavatele
Keywords: energetické zdroje; power resources; elektronické knihy; slovníky; electronic books; dictionaries